Improving Students' Interest in Learning Mathematics as an Effect of Covid-19 Pandemic through Cooperative Model Peer Tutor Technique - Rahma Wati; Macharani Adi Putri Siregar (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study aims to increase students' interest in learning mathematics covid-19 pandemic effects through a cooperative model of peer tutoring techniques. The subjects of this study were students of class XI IPA I SMA Muhammadiyah 09 Aek Kanopan, totaling 30 students.  The method used is quantitative research experimental research design, which aims to increase students' interest in learning. With the cooperative method of peer tutor technique, students are expected to be more active in discussing in groups during the learning process. At the same time, the teacher acts as a moderator or facilitator. Proven by a questionnaire analyzed and expressed in the form of a percentage calculated using the average value percentage formula. The results showed that students' interest in learning increased from 51.05% to 80.30%. It is clarified by student learning outcomes from 5 students who can answer questions from 30 students. This shows that students' interest in learning has increased. Researchers recommend this peer tutor method to be part of the mathematics learning strategy at the high school level. The schools and the teachers can consider applying this model as part of a more effective learning approach.